PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA HOTEL WINSTAR PEKANBARU - Dwina Andita Khairunnisa; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at Hotel Winstar Pekanbaru located on Jalan M Ali No. 118. Pekanbaru, Riau. The purpose of this study was to determine the effect of service quality and pricing on hotel customer satisfaction at Hotel Winstar Pekanbaru partially and simultaneously. In this research, the method used is descriptive quantitative analysis with SPSS program. The population in this study were hotel guests who stayed at the Winstar Hotel Pekanbaru in the last year, 2020 as many as 10,545 people. Where the sample in this research is the consumers of Hotel Winstar Pekanbaru as many as 100 respondents. To determine the sample using the Slovin formula. Data collection techniques through questionnaires, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. From data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial), and f test (simultaneous). The results of this study indicate that the results of testing the first t test hypothesis, service quality on customer satisfaction, namely t count (8.280) > t table (1.6605), meaning that service quality has a significant effect on customer satisfaction. Second, pricing on consumer satisfaction is t count (8,190) > t table (1,6605) meaning that pricing has a significant effect on consumer satisfaction. The results of the f test of service quality and price have a significant effect on consumer satisfaction, namely f count (48.925) > F_table (3.09). This means that the quality of service and pricing simultaneously have a significant effect on customer satisfaction at Winstar Hotel Pekanbaru Keywords: Service Quality, Price, Consumer Satisfaction